A retrospective study of changes in skin cancer characteristics over 11 years - Park, Young Ji (Arch Craniofac Surg, 2020)
BACKGROUND: The incidence of skin cancer, which is primarily caused by exposure to ultraviolet radiation, has steadily increased in recent years. The authors of the present study sought to investigate changes in the epidemiology of skin cancer by conducting a retrospective review of patients diagnosed with skin cancer who received related care at a single medical institution. METHODS: The present study included patients who were diagnosed with skin cancer and received treatment at Gyeongsang National University Hospital from 2008 to 2018. The site and type of skin cancer, the number of patients with skin cancer each year, the sex and sex ratio of the patients, and changes in patients’ age at first diagnosis were examined through retrospective chart reviews. RESULTS: The number of patients with skin cancer significantly increased, but statistically significant changes were not found in patients’ sex, skin cancer sites, or the types of skin cancer. However, patients’ age at the first diagnosis of skin cancer showed a statistically significant decrease starting in 2015. CONCLUSION: In this study, the number of patients with skin cancer increased over time. However, patients’ age at first diagnosis has decreased since 2015. Therefore, younger patients should take care to prevent skin cancer, and further research on the causes of skin cancer in younger patients is needed.